Tooth wear in patients submitted to bariatric surgery - Alves,Maria do Socorro Coêlho (2012)
Bariatric surgery may cause frequent vomiting episodes and gastroesophageal reflux, which promote the contact of gastric acids with the teeth leading to irreversible loss of tooth structure. The aim of this study was to assess prevalence of tooth wear in bariatric patients. One hundred and twenty-five patients were examined at a Public Hospital in São Luis, MA, Brazil, between July and October 2010, being patients who had already been submitted to the bariatric surgery at least 6 months previously (Bariatric group), morbidly obese patients who were on the waiting list for this surgery (Obese group) and patients who were waiting for ambulatory medical care in other sectors (Control group). The patients answered an investigative questionnaire and were clinically examined using the Basic Erosive Wear Examination (BEWE) scoring system, which allows the classification of the severity of noncarious dental lesions (NCDL) and evaluation of risk. All patients presented some degree of tooth wear at different levels. However, the presence of NCDL was associated with the group to which the patient belonged. The bariatric patients showed higher prevalence and a statistically significant level of risk with regard to NCDLs when compared with the other patients, followed by the obese and control groups. Reflux and vomiting did not seem to influence NCDL positively.